BONE REGENERATION - Tsilenko, O. (World of Medicine and Biology, 2015)
Regeneration is a process of restoring the biological object structure after its damage. There are three types of bone regeneration: physiological, reparative and the pathological one. Physiological regeneration is related to continuous restoring the bone structure elements which were lost during its vital activity, i.e. it is the structural rearrangement of the bone. Reparative regeneration is bone restoration after the injury, which includes surgical injury. Pathological regeneration is related to the disordered reparative or physiological function. The main mechanism of the physiological regeneration is represented with the oppositional growth of the bone which may be explained as follows: osteoclasts reabsorb the bone to 50 μm (the process takes 10 days), then osteoblasts create the organic matrix and its mineralization proceeds (during 80 days). After this the rest period follows and it may last up to 25 years. The physiological regeneration inducing factors are: changes in functions or exercise load, hormonal changes as well as endogenous electrical bone signals. An injury is one of the triggers initiating all reparative regeneration stages. In thebone tissue injury region during 24-48 hours there develops an inflammatory reaction in which the biological active substances are produced. The activity of the last causes arterioles, venules and capillaries to dilate, enhances vascular permeability, increases the capillary blood flow in the injured region. The exudate which is rich in proteins leaks into the tissues. It also consists of the cells such as neutrophils, macrophages and lymphocytes. The neutrophils produce cytotoxins which damage the cells and phagocyte them. An increased neutrophils presence in the tissues provides for the rough scar tissue formation. The function of macrophages doesn’t include only phagocytosis of the affected cells, but stimulation of the blood vessels growth within the affected region as they produce the angiogenic factor. The macrocirculatory stream is restored on the third day. By this time lymphocytes and their T-fraction regulate the osteogenic predecessor cells which start differentiating into osteoblasts. As the blood flow restores, they are supplied with nutrients, vitamins, microelements and oxygen. The osteoblasts start synthesizing the collagen matrix, non-collagen proteins (osteonectin and osteocalcin) and glycosaminoglicans. Osteonectin regulates mineralization of the organic bone matrix into which the osteoblasts are embedded, to turn into the osteocytes further. Osteocalcin regulates migration and activation of the osteoclasts which resorb the bone within the injured region. This process occurs on the 7th day after the injury. As a result of the osteoclasts activity, osteoinducers are released (e.g. morphogenetic bone proteins), and they produce inducible influence onto the perithelial cells (pluripotential cells). They transform into preosteoblasts, before their differentiation into osteoblasts they undergo about 50 division cycles. In case of fracture the cell elements of the areas adjacent to the injured region die, the main bone substance is demineralized. The induction inhibition disappears and the osteogenic predecessor cells respond onto the stimulating activity of the osteogenesis inducers. The demineralized bone matrix is a factor which stimulates the inducible osteogenesis. This is the way the osteogenesis induction occurs and this leads to the inducible osteogenic predeccessor cells repopulation increase.